Restrictive dermopathy: report of one case and the metabolic and post-mortem findings - Chiang, Ming-Chou; Huang, Shiu-Feng; Hsueh, Chuen; Lai, Ming-Wei; Hou, Jia-Woei (The Turkish Journal of Pediatrics, 2008)
Restrictive dermopathy is a rare and lethal autosomal recessive genodermatosis characterized by tight skin, typical dysmorphic face, generalized arthrogryposis and pulmonary hypoplasia. Infants with restrictive dermopathy have similar findings in skin biopsy, but other abnormalities are unremarkable. We report a male preterm infant with restrictive dermopathy. The post-mortem examination revealed hypoplasia of the thymus, and the metabolic study of the urine and blood disclosed generalized organic aciduria and low free carnitine level. These data imply that restrictive dermopathy is associated with certain degrees of metabolic disturbance. With increasing reports of restrictive dermopathy, the affected infants can be diagnosed earlier and accurately.